AB0034 Igg Subclass Composition of Autoantibodies to Two Novel Peptides in Early and Seronegative Rheumatoid Arthritis. (9th June 2015) - De Winter, L.; Quaden, D.H.; Hansen, W.; Lenaerts, J.; Geusens, P.; Stinissen, P.; Somers, V.
Abstract : Background: Previously, we identified autoantibodies to novel University of Hasselt (UH) peptides in early and seronegative rheumatoid arthritis (RA) 1 . Autoantibody responses against two of these peptides, UH-RA.1 and UH-RA.21, were validated in two large European cohorts (Hasselt University (UH) and Leiden Early Arthritis Clinic cohorts), resulting in the identification of 18-22% of RF-negative and ACPA-negative RA patients and up to one third of early RA patients. Since all immunoglobulins (Ig) exert different effector functions, either pro- or anti-inflammatory, investigating these Ig isotypes and subclasses can provide insight into the underlying complex humoral immune responses. Objectives: Our primary aim is to study the isotype composition of the autoantibody response against novel peptides in RA. Here we report the IgG subclasses for the anti-UH-RA.1 and anti-UH-RA.21 antibody responses. Methods: We selected all UH-RA.1 and UH-RA.21 IgG positive RA patients, and rheumatic and healthy controls from previous validation screenings on the UH cohort for further study of the IgG subclass distribution (IgG1-4): for UH-RA.1 we screened 18 RA patients and 10 controls, for UH-RA.21 53 RA patients and 19 controls. Additionally, similar numbers of UH-RA.1 and UH-RA.21 IgG negative samples were tested. Determination of target-specific IgG and its subclasses was performed by an in-house peptide ELISA. Results: Isotyping of the autoantibodies against UH-RA.1 revealed that most patients had IgG3, except for one RA patient, which presented with IgG1. Another RA patient also carried IgG2. Antibodies against UH-RA.21 showed a more diverse isotype distribution: IgG2 and IgG3 were most represented as they were found in 60% and 31%, respectively, of the antibody positive samples. To a lesser extent, IgG1 and IgG4 were also present (11% and 4%, respectively). Similar IgG subclass patterns were observed in RA patients and controls. Conclusions: Upon isotyping anti-UH-RA.1 antibodies, we observed that the vast majority of the patients had IgG3. For anti-UH-RA.21 antibodies, the predominant IgG subclasses are IgG2 and IgG3. As IgG3 is a well-known activator of the complement cascade, these antibodies could have pathogenic potential. Pro- and anti-inflammatory effector functions of these IgG subclass antibodies, together with the target-specific IgA and IgM isotypes, will be further investigated in order to prove their pathologic relevance. Additionally, we will evaluate whether differential isotype distribution among patients and controls might be of added diagnostic or prognostic value. References: Somers K, et al. J Autoimmun 2011 Feb;36(1):33-46. Disclosure of Interest: None declared